Prevalence of intestinal parasitic infections among highland and lowland dwellers in Gamo area, South Ethiopia - Wegayehu Teklu; Tsalla Tsegaye; Seifu Belete; Teklu Takele (BMC, 2013)
Abstract Background Epidemiological information on the prevalence of intestinal parasitic infections in different regions is a prerequisite to develop appropriate control strategies. Therefore, this present study was conducted to assess the magnitude and pattern of intestinal parasitism in highland and lowland dwellers in Gamo area, South Ethiopia. Methods Community-based cross-sectional study was conducted between September 2010 and July 2011 at Lante, Kolla Shelle, Dorze and Geressie kebeles of Gamo Gofa Zone, South Ethiopia. The study sites and study participants were selected using multistage sampling method. Data were gathered through house-to-house survey. A total of 858 stool specimens were collected and processed using direct wet mount and formol-ether concentration techniques for the presence of parasite. Results Out of the total examined subjects, 342(39.9%) were found positive for at least one intestinal parasite. The prevalence of Entamoeba histolytica/dispar was the highest 98(11.4%), followed by Giardia lamblia 91(10.6%), Ascaris lumbricoides 67(7.8%), Strongyloides stercoralis 51(5.9%), hookworm 42(4.9%), Trichuris trichiura 24(2.8%), Taenia species 18(2.1%), Hymenolepis nana 7(0.6%) and Schistosoma mansoni 1(0.12%). No statistically significant difference was observed in the prevalence of intestinal parasitic infections among lowland (37.9%) and highland dwellers (42.3%) (P = 0.185). The prevalence of intestinal parasitic infection was not significantly different among the study sites but it was relatively higher in Geressie (42.8%) than other kebeles. Sex was not associated with parasitic infections (P = 0.481). No statistically significant difference of infection was observed among the age groups (P = 0.228) but it was higher in reproductive age group. Conclusions The high prevalence of intestinal parasitic infections among the lowland and highland dwellers in Gamo area indicated that parasitic infections are important public health problems. Thus, infection control measures and the development of awareness strategies to improve sanitation and health education should be considered.